Research on tooth wear of non-spherical single-cone bit in hard rock formation of deep well. (July 2021) - Guo, Zhengwei; Deng, Rong
Highlights: Tooth breaking rock is simulated by finite element method, and the tooth load is tested. The tooth load, the cutting trajectory shape of each tooth and the contact time between tooth and rock are calculated. The theory model of tooth wear calculation is derived and compared with the experimental results. Abstract: Single-cone bit are an important tool for slim-hole drilling. In view of the problems of drilling with a spherical single-cone bit, a new non-spherical single-cone bit is designed that breaks rock by impacting and scraping. The field experiment test show that the tooth at the small end of the cone was severely worn, and the tooth at the large end of the cone was minimally worn. To determine the cause of the eccentric bit wear, the tooth breaking rock was simulated using the finite element method. The tooth load, the cutting trajectory shape of each tooth, and the contact time between the tooth and rock were analysed. The theoretical model of tooth wear calculation was derived and compared with experimental results. The results showed that the tooth load at the large end of the cone was greater than the tooth load at the small end of the cone, but the contact time at the small end of the cone was longer. The field test results showed that the No. 6 tooth wear was small, and No.1, No.4 and No.5 was smaller. The No.3 tooth was the most severely worn. The results from theoretical model were consistent with the field test results indicating that the tooth wear theory formula can predict tooth wear.